ALTERNATIVES FOR MAIZE SELECTION HYBRIDS INVOLVING SEVERAL TRAITS FOR SILAGE PRODUCTION - MAXIMILIAN DE SOUZA GOMES; RENZO GARCIA VON PINHO; MAGNO ANTONIO PATTO RAMALHO; DANIEL FURTADO FERREIRA (Revista Brasileira de Milho e Sorgo, 2006)
Searching for alternatives for selection of maize hybrids involving simultaneously several traits is desirable in any breeding program. This work was carried out to estimate heterosis and the effects of parents using multivariate diallel analysis as well as other methodologies which help distinguishing superior hybrids on the basis of selection for several characters. For this purpose, 6 high digestible and 6 low digestible lines were used in a 6 x 6 partial diallel plus the parental lines. Seeds from 36 hybrids and parental lines were sown in the experimental area of UFLA in two sowing seasons (November 4, 2001 and December 11, 2001). For each season, a 6 x 6 triple lattice was set up for the hybrids and a randomized block design with three replications for the 12 lines. Dry matter yield, grain yield, in situ dry matter degradability, and percentage of neutral detergent fiber were evaluated. From these four traits, multivariate diallel analysis was performed as well as a non-parametric selection index, called the graphic method, was applied. Only the hybrids of the diallel were used for this index. It was observed that multivariate diallel analysis results were similar to those of univariate diallel analyses. The results also corroborate, by multivariate diallel analysis, the importance of heterosis as well as the effects of parents in evaluating several characters simultaneously for maize silage production. The hybrid GNS 041 x GNS 079 provided good estimates of specific combining ability for traits, as well as the best performance by the graphic selection method. This hybrid has the potential to be used commercially for silage production. The graphic method for choosing cultivars considering a number of traits simultaneously is a good option for complementing multivariate diallel analysis.